Alkanna malatyana (Boraginaceae), a new species from East Anatolia, Turkey - Yildirim, Hasan; Şenol, Serdar Gökhan (Phytotaxa, 2014)
Alkanna malatyana (Boraginaceae) is described as a new species to science. It is endemic to the eastern Anatolia region of Turkey. A. malatyana is an obligated chasmophytic species, which colonizes on limestone rocky cliffs, known from a single locality in Levent Canyon, located in Malatya Province. It is related to A. mughlae and it shows some morphological similarities with A. confusa and A. kotschyana, but it clearly differs from them based on the morphological differences presented in the species description. In addition, the conservation status, a distribution map, and notes on the biogeography and ecology of the new species are given.